2021
DOI: 10.1093/mnras/stab2553
|View full text |Cite
|
Sign up to set email alerts
|

Fast galaxy bars continue to challenge standard cosmology

Abstract: Many observed disc galaxies harbour a central bar. In the standard cosmological paradigm, galactic bars should be slowed down by dynamical friction from the dark matter halo. This friction depends on the galaxy’s physical properties in a complex way, making it impossible to formulate analytically. Fortunately, cosmological hydrodynamical simulations provide an excellent statistical population of galaxies, letting us quantify how simulated galactic bars evolve within dark matter haloes. We measure bar lengths a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 83 publications
8
55
1
Order By: Relevance
“…Consequently, the angular momentum problem persists in the hierarchical cosmological ΛCDM framework and is unlikely to be solved by improving the resolution. This conclusion can also be reached independently through observed galaxy bars being fast with no sign of slowdown through Chandrasekhar dynamical friction on the hypothetical dark matter halo (Roshan et al 2021b). ΛCDM also faces many problems on other scales (Kroupa 2012(Kroupa , 2015Pawlowski 2021;Banik & Zhao 2022).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Consequently, the angular momentum problem persists in the hierarchical cosmological ΛCDM framework and is unlikely to be solved by improving the resolution. This conclusion can also be reached independently through observed galaxy bars being fast with no sign of slowdown through Chandrasekhar dynamical friction on the hypothetical dark matter halo (Roshan et al 2021b). ΛCDM also faces many problems on other scales (Kroupa 2012(Kroupa , 2015Pawlowski 2021;Banik & Zhao 2022).…”
Section: Discussionmentioning
confidence: 69%
“…In addition, secular processes like disk-halo angular momentum exchange could also drive the formation of significant bars and bulges in ΛCDM (Athanassoula 2002;Sellwood et al 2019), but perhaps not in the real universe (Banik et al 2020;Roshan et al 2021a) where the fraction of bars differs substantially from ΛCDM expectations (Reddish et al 2021). There is also a highly significant discrepancy between the pattern speeds of bars in observations and in ΛCDM simulations, where the results seem to have converged with respect to the ratio of bar length to corotation radius (Roshan et al 2021b). The tension is caused by the fact that bars are expected to be slowed down by dynamical friction with the dark matter halo, but observed bars are fast.…”
Section: Impact Of the Merger Historymentioning
confidence: 90%
“…This argument is statistical in nature, leaving plenty of room for some galaxies to have fast bars in ΛCDM. Indeed, many such cases are evident in figures 5 and 6 of Roshan et al (2021b). It is therefore not completely surprising that some studies found fast bars in the ΛCDM paradigm (e.g.…”
Section: Bar Pattern Speedmentioning
confidence: 89%
“…The final result of Roshan et al (2021b) is their figure 8, reproduced here as our Figure 18. The different ΛCDM simulations all give consistent results, but the region they converge on is strongly excluded observationally.…”
Section: Bar Pattern Speedmentioning
confidence: 97%
See 1 more Smart Citation